The influence of ethical leadership on turnover intentions: the mediating role of job satisfaction - M Abyan Syuja; Aryana Satrya (President University, 2022)
The service industry in the mechanical engineering field company where employees are required to have high accuracy and under close supervision, potentially feel great work pressure which can stimulate turnover intentions. There are problems in organizational culture cultivation and good governance implementation, thus potentially having low results of ethical leadership and job satisfaction, which resulted in high turnover intentions. This research aims to analyze the correlation between ethical leadership and organizational culture towards turnover intentions directly and through job satisfaction as an intervening variable and to analyze the mediation effect of job satisfaction on turnover intentions. The research method used is quantitative. Primary data are obtained directly from subjects through questionnaires. The populations are 524 employees. The sampling technique used census; thus, all populations can be used as research samples. Data are analyzed by pre-test and path analysis with Structural Equation Modelling. There is no directly proportional and significant correlation between independent variables towards mediation variables as well as inverse and significant correlation between independent variables and mediation variables towards dependent variables.